2014
DOI: 10.1136/bjsports-2014-093929
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during school hours when added to patient education improves outcome for 2 years in adolescent patellofemoral pain: a cluster randomised trial

Abstract: BackgroundPatellofemoral pain (PFP) is common among adolescents and associated with long-lasting pain and disability. Patient education and exercise therapy are commonly used treatments in primary and secondary care but the effect of these treatments in adolescents is unknown. We aimed to determine the effect of exercise therapy as an add-on therapy to patient education compared with education alone.Methods121 adolescents from 15–19 years of age were cluster randomised to patient education or patient education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
199
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(209 citation statements)
references
References 28 publications
4
199
2
4
Order By: Relevance
“…Others have also reported lower success rates (29%-53%) in adolescent patients with PFP. 12,19 It has been suggested that these differences in success rates with treatment may be due to differences in the characteristics of patients, including the longer duration of symptoms, the bilateral nature of symptoms, and the higher physical activity level in the adolescent population. While this study also shows that adolescents with PFP report a longer symptom duration, more bilateral symptoms, and a slightly higher physical activity level compared to adults with PFP, the outcomes of pain, function, and recovery did not differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have also reported lower success rates (29%-53%) in adolescent patients with PFP. 12,19 It has been suggested that these differences in success rates with treatment may be due to differences in the characteristics of patients, including the longer duration of symptoms, the bilateral nature of symptoms, and the higher physical activity level in the adolescent population. While this study also shows that adolescents with PFP report a longer symptom duration, more bilateral symptoms, and a slightly higher physical activity level compared to adults with PFP, the outcomes of pain, function, and recovery did not differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…1,19 Very little information has been reported on prognosis and treatment effectiveness in the adolescent population with PFP, as most studies have excluded this group. One exception is the work by Rathleff et al, 12 who reported that 62% of adolescents with PFP continue to have persistent symptoms at 1-year follow-up, despite the use of exercise therapy. This indicates that even at a very young age, symptoms can persist for a long period of time.…”
mentioning
confidence: 99%
“…Portanto, uma alternativa para lidar com esse problema é o aumento gradual da atividade física e treinamento com aumento gradual de cargas para melhor adaptação desses adolescentes às demandas biomecânicas necessárias durante atividades físicas [30]. Além disso, o tratamento dessa população por meio de exercícios com acompanhamento de um profissional da saúde parece ser efetivo na redução dos sintomas, auxiliando-os ao retorno das atividades físicas normais [12,30].…”
Section: Discussionunclassified
“…De acordo com Rathleff et al [10], mais de 1500 artigos científicos já foram publicados na área da DFP nos últimos 30 anos e menos de 5% desses estudos envolvem adolescentes. Na maioria dos casos, adolescentes com DFP apresentam sintomatologia de mais de três anos [11], e apenas 5% reportam duração da dor por menos de seis meses [12]. Além da dor a longo prazo, adolescentes com DFP reportam reduções no nível funcional e na qualidade de vida [13].…”
Section: Introductionunclassified
“…A randomized trial from Denmark demonstrated the efficacy of a comprehensive exercise and education program for treating ''adolescent patellofemoral pain,'' compared with education alone. 19 An analysis of Australian and Dutch cohorts showed that therapy was more likely to be successful when the pain was of recent onset and less severe in intensity. 2 As the nonspecific nature of the term implies, anterior knee pain is not monolithic, and certain subgroups may be more responsive to specific treatments.…”
Section: Editorialmentioning
confidence: 99%